The Effectiveness of Antenatal Corticosteroids Administration in Women at Risk for Late Pre-Term Delivery [38H]. (May 2018) - La Rosa, Mauricio; Kirsch, Nathan; Florence, Elizabeth; Petruzzi, Victoria; Saade, George R.; Saad, Antonio
Abstract : INTRODUCTION: The objective of this study was to determine the effectiveness of antenatal corticosteroid (ACS) administration to late preterm pregnancies, and associated adverse neonatal outcomes, after implementation of this policy at our institution. METHODS: Retrospective cohort of women with late preterm delivery during 2015 -2017. We compared patients before and after the implementation of the 2016 recommendations. The primary outcome was a composite of perinatal morbidity defined as: CPAP or high-flow nasal cannula for at least 12 continuous hours, supplemental oxygen with a fraction of inspired oxygen of at least 0.30 for at least 24 continuous hours, ECMO or mechanical ventilation, stillbirth, or neonatal death within 72 hours after delivery. Other neonatal outcomes included respiratory distress syndrome (RDS), transient tachypnea of the newborn (TTN), apnea, bronchopulmonary dysplasia (BPD), surfactant administration, need for resuscitation at birth, severe respiratory morbidity, and neonatal hypoglycemia (serum glucose ⩽ 40 mg/dL). Univariable and multivariable logistic regression analyses were performed and a P<0.05 was considered statistical significant. RESULTS: Of 602 patients, 239 received at least one dose of ACS. The composite outcome was not significantly different between those who received versus those who did not receive ACS (1.13 95%CI [0.8-1.6] p=0.46]). All the secondary outcomes were not different between groups. Neonates in the steroid group did not have a significantly higher rate of hypoglycemia (1.28 95%CI [0.77-2.12] p=0.29). The lack of differences persisted after adjusting for potential confounders. CONCLUSION: We were unable to find neonatal benefit, nor increased hypoglycemia, after introduction of ACS for late preterm delivery.